Gender differences in treatment with antidepressants during first weeks of a sick-leave spell due to depressive episode. (27th September 2019) - Lytsy, Per; Alexanderson, Kristina; Friberg, Emilie
Abstract: Background: The incidence of depression is higher in women; women are more often on sick leave due to depression, and more women than men use antidepressants. The objective of this study was to explore possible gender differences in buying prescribed antidepressants during the first 21 days of a new sick-leave spell due to depressive episode. Methods: Included were all individuals living in Sweden in working age (18–64 years old) who in 2010 or 2011 began a new sick-leave spell due to depressive episode (ICD-10 F32) lasting at least 21 days ( n = 44 863). Register data on sociodemographics, morbidity and dispensed prescription medication were used to investigate associations between gender and buying prescribed antidepressants in the total group and in subgroups, using multiple logistic regression models. Results: The study population consisted of 69.5% women. Within the first 21 days of the sick-leave spell, 48.0% of the men and 42.1% of the women had dispensed prescribed antidepressants. In the adjusted multiple logistic regression model, men had an odds ratio of 1.28 (95% confidence interval 1.23–1.33) as compared with women, for buying prescribed antidepressants. Conclusions: In this nationwide register study, nearly half of the women and men on sick leave with depressive episode bought prescribed antidepressants during the first three weeks of the sick-leave spell. In the adjusted models, men were more likely to do this. Further studies are needed to elucidate the reasons for this gender difference.